2009
DOI: 10.1002/ps.1868
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of quinate in the mode of action of glyphosate and acetolactate synthase inhibitors

Abstract: Quinate accumulation was a common effect of the two different classes of herbicide. Moreover, exogenous quinate application had phytotoxic effects, showing that this plant metabolite can trigger the toxic effects of the herbicides. This ability to mimic the herbicide effects suggests a possible link between the mode of action of these herbicides and the potential role of quinate as a natural herbicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
128
2
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(158 citation statements)
references
References 46 publications
20
128
2
7
Order By: Relevance
“…Although the photosynthetic process is not the primary target of glyphosate in plants, some studies have shown a reduction in A triggered by this herbicide (Duke et al, 2003;Mateos-Naranjo et al, 2009;Orcaray et al, 2010), which supports the results of this study. Yamada and Castro (2007) postulated that the reduced efficiency of gas exchange due to glyphosate is associated with dysregulation of stomatal closure and thus with changes in the opening and closing of stomata.…”
Section: Discussionsupporting
confidence: 91%
“…Although the photosynthetic process is not the primary target of glyphosate in plants, some studies have shown a reduction in A triggered by this herbicide (Duke et al, 2003;Mateos-Naranjo et al, 2009;Orcaray et al, 2010), which supports the results of this study. Yamada and Castro (2007) postulated that the reduced efficiency of gas exchange due to glyphosate is associated with dysregulation of stomatal closure and thus with changes in the opening and closing of stomata.…”
Section: Discussionsupporting
confidence: 91%
“…The potassium phosphite treatments with or without glyphosate showed higher tryptophan levels and did not alter the phenylalanine and tyrosine contents in the plants. (Harring et al 1998, Singh & Shaner 1998, María et al 2006, Buehring et al 2007, Nandula et al 2007, Petersen et al 2007, Matallo et al 2009, Orcaray et al 2010, Reddy et al 2010, Zelaya et al 2011, Franco et al 2012. Os elevados níveis de ácido chiquímico são utilizados como indicador precoce e altamente sensível dos efeitos do glyphosate nos tecidos das plantas (Harring et al 1998).…”
unclassified
“…Os elevados níveis de ácido chiquímico são utilizados como indicador precoce e altamente sensível dos efeitos do glyphosate nos tecidos das plantas (Harring et al 1998). O ácido quínico, composto de estrutura semelhante à do ácido chiquímico, também pode ser acumulado em plantas expostas ao glyphosate (Orcaray et al 2010e 2012, Carbonari et al 2014.…”
unclassified
“…A three-to four-fold variation in ALS gene expression has been reported in several tobacco organs such as leaves, seedlings, and flowers [37]. An increase in the free amino acid pool after the application of ALS-inhibitors has been reported [38] [39] [40]. This increased protein pool was attributed to an increase in protein turnover rates in response to treatment with ALS-inhibitors [41].…”
Section: Expression Of Target-site Genes Upon Herbicide Treatmentsmentioning
confidence: 99%